Entre lágrimas e risos: os serelepes e a memória do teatro itinerante - Santos, Elaine dos (2013)
This paper presents a study about the traveling theater, doing it on the bias of melodramatic texts represented during the years 1940 to 1980 and that, in actuality, fell in disuse as a result of competition, especially from soap operas. In general, there was a concern to demonstrate that, although the melodrama is considered to be a minor genre, without literary valuation, it follows the Aristotelian precepts that validate it as an aesthetic representation and, therefore, compared it with other artistic -literary manifestations that outlined the so called cultural universe throughout the centuries. More closely, the focus is on melodrama, its origin, critical appreciation, the success of public specially in the years subsequent to its appearance, after the French Revolution and the morality school - opposing good and evil that this genre has always cultivated. Later, the study turned to the Theatre Serelepe, its history, the plays performed, presenting a summary of them to facilitate the analytical approach of this corpus, contextualizing it in the world of literature as a whole (structure, theme, among other aspects). The methodology used was of descriptive and bibliographical nature, relying on scholars that address the dominant themes and description of the plays and activities of the traveling theater. Finally, collaborations and limitations that the traveling theater gave rise to over the years were pointed out, particularly during the period in which the melodramas were the main attraction of their shows, dominated today by farces, comedies, comedy sketches.